2002
DOI: 10.1093/ndt/17.12.2087
|View full text |Cite
|
Sign up to set email alerts
|

Nephrology, dialysis and transplantation in Turkey

Abstract: The establishment of the Turkish Society of Nephrology (TSN) in 1970 coincided with that of many western European nephrology societies. The TSN organized the 15th ERA-EDTA Congress in Istanbul in 1978, earlier than many European Countries, and currently has 286 active members. At present, Turkey has 161 nephrologists, which equals 2.5 nephrologists per million population (p.m.p.). The number of original articles submitted by Turkish authors to the journal Nephrology Dialysis Transplantation ranks 7th-8th among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…42 It may be that over time patients also begin to accept and adapt to the treatment regimen, which may positively impact fatigue. 77 In contrast, Letchmi et al 78 found a significant relationship between fatigue and dialysis vintage, with patients who had undergone treatment for more than 2 years experiencing high levels of fatigue. An explanation for the latter findings may be that, although with time patients become accustomed to the dialysis routine, their coping mechanisms in response to symptoms may remain unchanged.…”
Section: Treatment Modality and Fatiguementioning
confidence: 96%
“…42 It may be that over time patients also begin to accept and adapt to the treatment regimen, which may positively impact fatigue. 77 In contrast, Letchmi et al 78 found a significant relationship between fatigue and dialysis vintage, with patients who had undergone treatment for more than 2 years experiencing high levels of fatigue. An explanation for the latter findings may be that, although with time patients become accustomed to the dialysis routine, their coping mechanisms in response to symptoms may remain unchanged.…”
Section: Treatment Modality and Fatiguementioning
confidence: 96%
“…Huang et al, compared complications associated with the PD method in 247 patients. Peritonitis incidence was signifi cantly lower in APD compared to CAPD patients (p<0.001) and diabetes had no impact on peritonitis (9). Newly developed Y systems and new communications systems that operate with "washing before fi lling" lowered the peritonitis incidence in CAPD patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of patients who started to receive RRT in 2014 according to the type of RRT shows that 78.37% (55,890) of the patients received hemodialysis (HD) [1]. According to this data, Turkey ranks fifth among European countries in terms of patient populations receiving HD treatment [2].…”
Section: Introductionmentioning
confidence: 99%